Bovine Viral Diarrhea Virus Infection in Cattle - Antioxidant Status and Some Biochemical Parameters - Halil Simsek,; Metin Gurcay,; Merve Ozturk,; Hakan Kececi, (Acta Scientiae Veterinariae, 2023)
Background: Bovine viral diarrhea virus (BVDV) infections in cattle result in significant economic losses due to reproductive performance deficiencies caused by gastrointestinal, respiratory system infections, and transplacental infections. BVDV is one of the most important and widespread pathogens in cattle worldwide, including Turkey. Methods such as virus neutralization, enzyme-linked immunosorbent assay (ELISA), reverse transcriptase and polymerase chain reaction (RT-PCR) are used for the detection of the disease. The diagnosis of the disease in its subclinical form is challenging due to the lengthy and costly procedures involved. Investigating oxidative stress parameters in ruminants with various diseases contributes significantly to diagnosis and prognosis. This study aimed to investigate some oxidative stress and biochemical parameters in cattle infected with BVDV. Materials, Methods & Results: In the study, blood samples were collected from 80 Simmental breed cows aged between approximately 4 and 8 years to determine the presence of BVDV antibodies using the ELISA method. Based on the results obtained, study groups were organized. The study included a group of 10 animals with positive antibody levels as the infected group, and a group of 10 animals with negative antibody levels as the healthy group. Blood samples were taken from the animals, and serum separation was ensured. In the obtained serum samples, levels of vitamin E, vitamin A, β-Carotene, catalase, GSH-Px, and MDA were determined using spectrophotometric methods. In addition, serum total protein, albumin, alkaline phosphatase (ALP), aspartate aminotransferase (AST), glucose, low-density lipoprotein (LDL), high-density lipoprotein (HDL), calcium (Ca), and phosphorus (P) were measured using commercial test kits and an autoanalyzer. In the study, it was observed that the differences in serum MDA, vitamin E, vitamin A, β-carotene, and catalase levels were statistically significant between the healthy and BVDV-infected groups (P < 0.001). The activity of GSH-Px was also found to be statistically different between the groups (P < 0.01). Among the biochemical parameters, HDL, LDL, and AST levels were found to be statistically significant between the healthy and BVDV-infected groups (P < 0.001). Additionally, ALP and glucose levels were found to be statistically significant (P < 0.01). However, although there were differences in the levels of total protein, albumin, Ca, and P between the groups, these results were not statistically significant. Discussion: Although the diagnosis of the disease was partially made based on clinical observations in BVDV infections, the ELISA method was used for accurate diagnosis. Furthermore, it was found that there was a significant difference in MDA concentration between the healthy and infected groups, indicating oxidative damage caused by the virus. Similarly, significant differences in vitamin E, vitamin A, β-carotene, GSH-Px, and catalase levels were observed between the groups, indicating a decrease in antioxidant values due to the infection. In addition, differences in ALP, AST, glucose, LDL, and HDL levels were found between the groups. This difference is thought to be related to the effects of the disease agent on the liver and systemically. This study demonstrates that, in addition to the viral pathogen, antioxidant and biochemical values are important criteria in the detection of the disease. Keywords: antioxidant, bovine, BVDV, MDA, serum biochemistry.